Poly(vinyl alcohol)/gelatin Hydrogels Cultured with HepG2 Cells as a 3D Model of Hepatocellular Carcinoma: A Morphological Study - Stefania Moscato; Francesca Ronca; Daniela Campani; Serena Danti (Journal of Functional Biomaterials, 2015)
It has been demonstrated that three-dimensional (3D) cell culture models represent fundamental tools for the comprehension of cellular phenomena both for normal and cancerous tissues. Indeed, the microenvironment affects the cellular behavior as well as the response to drugs. In this study, we performed a morphological analysis on a hepatocarcinoma cell line, HepG2, grown for 24 days inside a bioartificial hydrogel composed of poly(vinyl alcohol) (PVA) and gelatin (G) to model a hepatocellular carcinoma (HCC) in 3D. Morphological features of PVA/G hydrogels were investigated, resulting to mimic the trabecular structure of liver parenchyma. A histologic analysis comparing the 3D models with HepG2 cell monolayers and tumor specimens was performed. In the 3D setting, HepG2 cells were viable and formed large cellular aggregates showing different morphotypes with zonal distribution. Furthermore, β-actin and α5β1 integrin revealed a morphotype-related expression; in particular, the frontline cells were characterized by a strong immunopositivity on a side border of their membrane, thus suggesting the formation of lamellipodia-like structures apt for migration. Based on these results, we propose PVA/G hydrogels as valuable substrates to develop a long term 3D HCC model that can be used to investigate important aspects of tumor biology related to migration phenomena.